K+-9=-6

Simple and best practice solution for K+-9=-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for K+-9=-6 equation:


Simplifying
K + -9 = -6

Reorder the terms:
-9 + K = -6

Solving
-9 + K = -6

Solving for variable 'K'.

Move all terms containing K to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + K = -6 + 9

Combine like terms: -9 + 9 = 0
0 + K = -6 + 9
K = -6 + 9

Combine like terms: -6 + 9 = 3
K = 3

Simplifying
K = 3

You can always share this solution

See similar equations:

| 50=4k+6 | | 200-10=20x-90 | | 40=4+9h | | 2Kx-3X+4=0 | | 5x+350=5 | | 39+8x=-3(7-4x)+6x | | 15x-5=65 | | 5x+2x=15 | | -12n-15=-3 | | 5x+100=3x+122 | | -10/9-(-1/6) | | 5s+50=10 | | -133=8+3(6b-5) | | -3/7x=4 | | 4-16+3= | | -3/4x=4 | | 2n-14=-60 | | 2x+4y+6z= | | -5/2r=12 | | 65432346790987654323-98765433456780= | | x^22+10x-300=0 | | 15m+3n-6m+7n= | | 0.6=8.5+2.1*m | | p+29=2p | | X-7x+2x-5x= | | 4x+15=5+6x | | -96=-6(1+3x) | | 7-8(6a-4)=279 | | (-6)/4-x=(2x)/x-2 | | s=p/18 | | 93=-3(-4x-7) | | 5x+10=3x+8 | | 2+3h=-22 | | t-23=5 | | f(2)=2x^4-5x^2-3x+2 | | 2x^2+12x-8x=0 | | 18z-20=19z+80 | | 109=7+3(6m-8) | | 16x+5=18x-7 | | 73x=180 | | 248=8+10(9x-3) | | 20g+25=-55 | | -18x+7=43 | | b+40=70 | | f(x)=8x^2-2x-3 | | -9+3x=21 | | x-7x=-8x-14 | | 18+3x=21 | | 18+3x=211 | | 2000000/4000000 | | y=6E+06x | | 26x-28x=10-12 | | 10x-(4x+3)+7=4x | | x/7-6=-4 | | -4x+9-10=8x-12-x | | 12-w=8 | | -2(x-7)=-2+15 | | -3k+7k=-4+k+k | | x^2+1.8x-3.19=0 | | 4^3/2^3 | | 18+b=32 | | KxSquared-3X+4=0 | | 4y^2+100= | | x-35=39 | | 2x-11=5-6x |

Equations solver categories